The Role of Village-Owned Enterprises (BUMDES) in Improving Community Welfare in Bontomanai Village, Bajeng Barat District, Gowa Regency - Izzati Qur'aini, Dzul; Sakawati, Herlina; Kasmita, Maya (Jurnal Administrasi Bisnis, 2025)
This research examines “the Role of Village-Owned Enterprises (Bumdes) in Improving Community Welfare in Bontomanai Village, West Bajeng District, Gowa Regency, Gowa Regency. The research method used was qualitative with a descriptive approach, conducted in BontomanaiVillage, West Bajeng District, Gowa Regency. Primary and secondary data are used as data sources, with data collection techniques including observation, interviews, and documentation. Data validity is verified through triangulation and member check. Data analysis is carried out through data reduction, data presentation, and conclusion. The results showed that BUMDes have a significant role in supporting the welfare of rural communities by providing various facilities. However, there are still shortcomings that need to be considered and corrected so that BUMDes can be more effective in helping to improve the economy of rural communities. BUMDes also act as mediators in improving community welfare, but are faced with challenges such as high levels of area and the need for follow-up actions to maximize the benefits of the BUMDes program. In addition, BUMDes also play a role in providing motivation and facilitation to rural communities to improve their welfare, with emphasis on management performance, commitment to vision and mission, and increasing available business capital.